ANALISIS FAKTOR PERILAKU KEUANGAN TERHADAP KEPUTUSAN INVESTASI EMAS MASYARAKAT KOTA BATAM - Budiman, Johny; Jasika, Jasika (Journal of Global Business and Management Review, 2019)
The purpose of this study is to investigate the influence of behavioral factors which consisting of regret aversion, overconfidence, loss aversion, heuristics and availability bias on gold investment decisions in Batam City investor. To conduct the study, a total of 250 questionnaires were issued and distributed to the investors of gold in Batam city. To test the hypothesis, multiple linear reggression analysis is used. The results of the research showed that regret aversion has a significant and positive effect and loss aversion has a negative significant influence on gold investment decisions. While there are no significant influence of overconfidence, heuristic and availability bias to investment decisions.